Breast augmentation using a free lateral thoracic artery perforator flap from the contralateral breast: A case report. Issue 2 (4th June 2021) - Sharp, Olivia L.; Köhler, Guido; Haywood, Richard M.; Masud, Dhalia
Abstract: When performing breast reconstruction, reduction of the contralateral breast is often required to achieve symmetry. The tissue that would otherwise be discarded from the reduced breast has been utilized as a free flap. This has the benefit of minimizing donor site morbidity, and combining the principles of "spare‐part‐surgery" and replacing "like‐with‐like." The purpose of this paper is to report the procedure, outcome, and potential controversies of using a free lateral thoracic artery perforator flap for contralateral breast reconstruction. We present a 32‐year‐old with congenital breast asymmetry previously corrected with an implant. The patient required tertiary breast reconstruction for capsular contracture, and a simultaneous left breast reduction. There was no history of breast cancer. The reconstruction proceeded as follows; the right sided breast implant was removed. On the left breast, a wise pattern reduction with a superomedial pedicle was instigated. Intraoperatively, four perforating arteriovenous pedicles perfusing the reduced tissue were identified; of which the lateral thoracic artery perforator was selected. The flap weight was 296 g. The lateral thoracic pedicle was anastomosed to the right internal mammary vessels. The flap survived completely. The post‐operative course was uneventful and without complication. The patient was followed up for 1 year and was pleased with the final result. The application of the LTAP free flap may cautiously be extended to oncological breast reconstruction. For patients to be suitable, they would need a large remaining breast to provide adequate tissue for reconstruction, up‐to‐date breast screening and a low risk of developing breast cancer in the future.